FAALİYETE DAYALI MALİYETLEME VE HASTANELERDE UYGULANABİLİRİĞİ: TEORİK İNCELEME - YILDIRIM, ESRA MERVE (Fırat Üniveristesi, 2017)
Literatür taramasında maliyet, gider, harcama kavramları ile faaliyet ve faaliyete dayalı maliyetleme kavramı anlatılmaya çalışılmıştır. Bu araştırmanın amacı, çalışma konusu olan Faaliyete Dayalı Maliyet Sistemi'nin diğer literatür kaynaklarla beraber incelenmesidir. Bu amaçla hastanelerde Faaliyete Dayalı Maliyetleme Sistemi'ni ele alan tez ve makalelerin sonuçları incelenmiş ve bu sonuçlar doğrultusunda; Faaliyete Dayalı Maliyetleme Sistemi'nin Geleneksel Maliyetleme Sistemi'nden farklı olduğu, mamul veya hizmetler üretim sırasında, gerçekleştirdiği her bir faaliyete ilişkin ayrı dağıtım anahtarları aracılığı ile yüklendiği için, Geleneksel Maliyet Sistemi'ne göre daha gerçekçi maliyet bilgilerini ortaya çıkmıştır. Anahtar Kelimeler: Maliyet, Faaliyet, Faaliyet Dayalı Maliyetleme

The concepts costing, expenses, costs and activities, and costing based on activities were attempted to be defined by scanning books and articles. The purpose of this study is to examine the subject of this study Costing Based on Activities together with other resources like books and articles. The results of academic dissertations and articles which approach Costing Based on Activities with this purpose at hospitals were examined, and in line with these results; it was discovered that the Costing Based on Activities system different from the Traditional costing system, and that because it was loaded through different allocation keys related with every activity during the items and service production, more down to earth cost data debouched in comparison with the Traditional Costing System. Key Words: Cost, Activity, Activity Based Costing
Activity based costing and applicability in hospitals: A theoretical review
Keywords: İşletme